Soluble CD163 and small dense LDL cholesterol levels in type 2 diabetes patients - Novida, Hermina; Adi Soelistijo, Soebagijo; Sutjahjo, Ari (Gaceta Médica de Caracas, 2021)
Introduction: The sdLDL cholesterol proportion is a better marker for the prediction of cardiovascular diseases (CVDs). Macrophages play a crucial role in both the initiation and progression of atherosclerosis, the underlying mechanism of CVDs. This study investigated the correlation between soluble CD163 as a biomarker macrophage activation and sdLDL cholesterol in type 2 diabetes mellitus (T2DM) subjects for the first time.